2003
DOI: 10.1046/j.1471-0528.2003.02216.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of domestic violence in pregnant women

Abstract: Objective To determine the prevalence of domestic violence in a population of pregnant women.Design Questionnaire survey.Setting Antenatal booking clinic in a north of England hospital.Population Five hundred consecutive women were included.Methods Anonymous confidential questionnaire to women who were not accompanied by their partners.Main outcome measures Disclosure of a past history of physical, emotional or sexual abuse.Results Four hundred and seventy-five questionnaires were returned (95% response rate).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
4
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 15 publications
5
69
4
7
Order By: Relevance
“…Studies have shown that a history of childhood sexual abuse ranges from 15% to 25% [18][19][20]. Multiple studies have examined the prevalence of physical abuse among women with ranges from 5% to 28% [21][22][23][24][25]. When comparing the above prevalence rates with those found among the IC sample, both depression and a history of sexual abuse were found to be statistically significant (P<0.05) (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Studies have shown that a history of childhood sexual abuse ranges from 15% to 25% [18][19][20]. Multiple studies have examined the prevalence of physical abuse among women with ranges from 5% to 28% [21][22][23][24][25]. When comparing the above prevalence rates with those found among the IC sample, both depression and a history of sexual abuse were found to be statistically significant (P<0.05) (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Scores range from 0 to 63 with higher scores representing more severe symptoms. Scores can be further stratified into categories of depression: mild depression (14)(15)(16)(17)(18)(19), moderate depression (20)(21)(22)(23)(24)(25)(26)(27)(28), and severe depression . A score of less than 14 is considered normal.…”
Section: Measurement Of Depressionmentioning
confidence: 99%
“…17 Using a modified version of Abuse Assessment Screen (AAS), one study from England showed the prevalence of violence against pregnant women to be 17%. 13 Other studies using Abuse Assessment Screen have indicated that 39.5% of pregnant women suffer from abuse. 8 The results of a study performed in a first step health clinic in Turkey showed that 24.9% of 101 pregnant women suffered from domestic violence.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,12,13,18 At the top of the questionnaire form, information about domestic violence during pregnancy was given. The questionnaire itself consisted of two parts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation